MORPHOLOGICAL AND CHEMICAL CHARACTERISTICS OF TWO SPECIES BELONG TO ALYSSEAE AND LEPIDIEAE TRIBES SPREAD IN NORTHERN IRAQ - Al-Abide, N. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This research was aimed to study three species which are prevalent in northern Iraq: Alyssium strigosum Banks and Sol., Clypeola jonthlaspi L, and Isatis tinctoria L. belonging to the Alysseae and Lepidieae tribes. The general characteristics of the roots, stems, leaves, fruits and seeds are studied and it turned out that and the two species A. strigosum and C. jonthlaspi are similar due to their belonging to the Alysseae tribe, and the species I. tinctoria differs since it belongs to the Lepidieae tribe. In addition, 6 secondary metabolites are diagnosed using the qualitative tests: alkalis, phenols, tannins, flavonoids, glycosides, and sapindales. The presence of terpenoids was not observed, and the alcohol extract is superior to the aqueous extract regarding the accuracy of the results. The phenols are detected using HPLC technology and four compounds are found: Rutin, Quercetin, Kaempferol and P-Coumarin. The importance of studying the chemical content comes from its use in subsequent studies and knowledge of its uses in the medical fields.